Voltage Sag Mitigation and Load Reactive Power Compensation by UPQC - P. Ajitha; D. Jananisri (Institute of Advanced Engineering and Science, 2014)
This paper presents Unified Power Quality Conditioner(UPQC) that consist of series inverter and shunt inverter in back to back configuration which simultaneously compensate the power quality(PQ) problems of both voltage sag and load reactive power compensation . In this paper ,Neural network is tool which is considered for solving power quality problems. The simulation results from MATLAB/SIMULINK are discussed to validate the proposed method.